Clinical course of paroxysmal dyskinesias throughout pregnancy. (November 2020) - Bovenzi, Roberta; Schirinzi, Tommaso; Pierantozzi, Mariangela; Stefani, Alessandro; Capuano, Alessandro; Mercuri, Nicola Biagio; Pisani, Antonio
Highlights: Both the clinical course and the management of PxDs in pregnancy are uncovered issues. Retrospective data show an improvement of movement disorder during pregnancy. Antidyskinetic drug discontinuation resulted in good pregnancy outcome in PRRT2 -PxD.